Design and fabrication of Nanowire-based conductance biosensor using spacer patterning technique - Uda, Hashim; Shahrir, Salleh; Siti Fatimah, Abd Rahman; Amir Razif Arief, Jamil Abdullah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org